2021
DOI: 10.51406/jhssca.v15i1.2089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compensation Practices on Academic Staff’s Job Performance in Federal University of Agriculture, Abeokuta, Ogun State, Nigeria

Abstract: The study examined the effect of compensation practices on academic staff’s job performance in Federal University of Agriculture, Abeokuta, Ogun State, Nigeria. Multi stage sampling technique was used to purposively select 3 Agricultural base colleges followed by proportionate stratified sampling technique where respondents were randomly selected. One hundred and three (103) respondents from the three colleges of agriculture of the university were selected of which 92 questionnaires were retrieved. Data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…This result has found a similar expression with the study of Ehichoya and Ogunode (2020) whose study discovered that an insufficient and unfair reward system amongst employees has led to several moments of dissatisfaction and consequently a poor QWL. Also, it takes a similar position with the study of Joshua et al (2020) whose outcome illustrated that insufficient and inequitable pay amongst university lecturers in the Federal University of Agriculture, Abeokuta in Nigeria led to moonlighting effect and brain-drain insurgency.…”
Section: Discussion Of Findingsmentioning
confidence: 80%
See 1 more Smart Citation
“…This result has found a similar expression with the study of Ehichoya and Ogunode (2020) whose study discovered that an insufficient and unfair reward system amongst employees has led to several moments of dissatisfaction and consequently a poor QWL. Also, it takes a similar position with the study of Joshua et al (2020) whose outcome illustrated that insufficient and inequitable pay amongst university lecturers in the Federal University of Agriculture, Abeokuta in Nigeria led to moonlighting effect and brain-drain insurgency.…”
Section: Discussion Of Findingsmentioning
confidence: 80%
“…Also, Ehichoya and Ogunode's (2020) study discovered that an insufficient and unfair reward system amongst employees has led to several moments of dissatisfaction and consequently a poor QWL. The study by Joshua et al (2020) showed that insufficient and inequitable pay amongst university lecturers in The Federal University of Agriculture, Abeokuta in Nigeria led to moonlighting effect. They all perceived a justification for a review of their compensation and also suggested that the government must involve academic staff in the decision-making process of their compensation and reward systems.…”
Section: Conceptual Review and Hypotheses Developmentmentioning
confidence: 99%